Breast Cancer: Reimbursement Policies and Adoption of New Therapeutic Agents by National Health Systems - Trapani, Dario (Breast Care (Basel), 2019)
BACKGROUND: Breast cancer is a cause of morbidity for more than half a million of patients in Europe, resulting in broad societal impacts that affect patients, families, and societies from a human, emotional, economic, and financial perspective. Expenditure for cancer medicines represents one of the principal driving costs of healthcare. The aim of this review is to describe the European policy and regulatory landscape of innovation uptake in breast oncology – with emphasis on value in cancer healthcare. SUMMARY: In Europe, several reimbursement models or policy tools have been developed by countries to compose their benefit packages. The most commonly applied scheme is the product-specific eligibility model, prioritizing selected medicines and their indications. Mixed models are commonly developed, addressing the protection of more vulnerable people, ensuring protection from impoverishment caused by cancer and containing disparities. However, the risk to incur significant out-of-pocket expenses for essential or newer medicines for cancer is still substantial in Europe, especially in low- and middle-income countries, determining greater financial distress and poorer outcome for patients. Value-based priority setting is an essential mechanism to ensure timely access to the most valuable medicines for breast cancer patients. Estimations of the value of medicines can be provided within health technology assessment services and networks and informed by benefit scales and tools. KEY MESSAGES: There is ample room for reciprocal support across the diverse cultural and legal realities in Europe. The aim is common: save cancer patients from premature death by ensuring the timely access to the best care, protecting from financial hardships and distress to leave no cancer patient behind in poverty. Steps are to be taken to promote value-based priority setting, paving the way toward universal health coverage in Europe, where health of people is protected, and affordable best quality care is the only standard pursued and acceptable.